The influence of ultrafine supplementary cementitious materials on the properties of Portland cements - Rusyn, Bohdan; Postolovskyi, Kostiantyn (Видавництво Львівської політехніки, 2013)
This paper describes the influence of ultrafine supplementary cementitious materials (SCM's) on the properties of Portland Cements. The combined using of ultrafine ground SCM's with polycarboxylate superplasticizer allows to obtain high flowability, physical and mechanical properties of Portland cements. Advanced interpretation of the ultrafine (SCM's) and their surface activity contributes the most complete realization of potential in binding properties of new types of Portland cements and producing High Performance Concretes on their base.
Keywords: ultrafine supplementary cementitious materials; Portland cements; flowability; cement paste; shrinkage